2021
DOI: 10.3390/molecules26030605
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Sutherlandia frutescens and Xysmalobium undulatum in LS180 Colorectal Cancer Mini-Tumors

Abstract: Colorectal cancer remains to be one of the leading causes of death worldwide, with millions of patients diagnosed each year. Although chemotherapeutic drugs are routinely used to treat cancer, these treatments have severe side effects. As a result, the use of herbal medicines has gained increasing popularity as a treatment for cancer. In this study, two South African medicinal plants widely used to treat various diseases, Sutherlandia frutescens and Xysmalobium undulatum, were evaluated for potential activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A recent paper published by Gouws et al [ 145 ] reported the use of a 2D Clinostat to tissue engineer 3D LS180 cell mini-tumors, suitable for drug testing. The authors tested the efficacy of the South African plants Sutherlandia frutescens and Xysmalobium undulatum in comparison to the standard paclitaxel treatment.…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
“…A recent paper published by Gouws et al [ 145 ] reported the use of a 2D Clinostat to tissue engineer 3D LS180 cell mini-tumors, suitable for drug testing. The authors tested the efficacy of the South African plants Sutherlandia frutescens and Xysmalobium undulatum in comparison to the standard paclitaxel treatment.…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
“…The literature survey revealed that several researchers have investigated the anticancer activity of S. frutescens . Research conducted by Gouws et al [ 86 ] showed that the aqueous extract of S. frutescens decreased LS180 colorectal cell growth and viability, with the IC 50 value of 2.63 mg/mL, as compared to paclitaxel, the positive control used in the study. Another study by Chinkwo [ 87 ] also revealed that the crude aqueous extract of S. frutescens showed significant cytotoxicity against neoplastic (cervical carcinoma) cells.…”
Section: Resultsmentioning
confidence: 99%
“…aculeastrum Itunga, Umthuma Solanaceae Fruits and leaves NT, NE A decoction is prepared from boiled fruit is filtered and then administered orally Breast cancer [ 98 ] 23 Sutherlandia frutescens L. R.Br. Umnwele Fabaceae leaves, flower and seed V, NE Decoctions are prepared from all the plant parts and administered orally Colorectal cancer [ 59 , 86 ] 24 Tulbaghia violacea Harv Utswelane Alliaceae Leave, bulb NT, E The fresh bulbs are boiled in water and the decoctions are taken orally Esophageal cancer [ 92 , 99 ] NT: neither rare nor threatened; V: vulnerable; E: endemic; NE: nonendemic, *: not available. …”
Section: Resultsmentioning
confidence: 99%
“…Infusions from the leaves and stems of these plants are traditionally used for cancer treatment [137]. A few scientific reports also exist to support its anticancer effects [141]. Interestingly, several studies have reported that its usage is not associated with any physiological toxicity, strengthening the rationale to evaluate its anticancer efficacy and mechanism of action further [135].…”
Section: Understudied Herbal Medicines As Potential Candidates For Cancer Metabolomics Studiesmentioning
confidence: 99%